Distribution of clay minerals in surface sediments of the western Gulf of Thailand: Sources and transport patterns. (1st June 2015) - Shi, Xuefa; Liu, Shengfa; Fang, Xisheng; Qiao, Shuqing; Khokiattiwong, Somkiat; Kornkanitnan, Narumol
Highlights: Clay mineral composition of surface sediment from Gulf of Thailand was reported. The GoT could be classified into three provinces due to clay mineral assemblages. Hydrodynamic conditions control the transport patterns of modern fine sediments. Abstract: A high density sampling program during two joint China–Thailand scientific cruises in 2011–2012 included collection of 152 gravity box cores in the Gulf of Thailand (GoT). Samples from the top 5 cm of each core were analyzed by X-ray diffraction for clay mineral content. Several systemic analytical approaches were applied to examine the distribution pattern and the constraint factors of clay minerals in the surface sediments of the western GoT. The clay minerals mainly comprise illite, kaolinite, chlorite and smectite, having the average weight percent distributions of 50%, 34%, 14% and 2%, respectively. Based on the spatial distribution characteristics and statistical results, the study area can be classified into three provinces. Province I contains high concentrations of smectite, and covers the northern GoT, sediments in this province are mainly from rivers discharging into the upper GoT, especially the Chao Phraya and Mae Klong Rivers. Sediments in Province II are characterized by higher values of illite, located in the central GoT, where fine sediments are contributed by the Mekong River and from the South China Sea. Province Ш, in the coastal regions of southwestern GoT close to Malaysia, exhibits a clay mineral assemblage with complex distribution patterns, and may contain terrestrial materials from the Mae Klong River as well as re-suspended sediments. Results of integrative analysis also demonstrate that the hydrodynamic environment in the study area, especially the seasonal various circumfluence and eddies, play an important role in the spatial distribution and dispersal of clay fraction in sediments.